Husband's Support Relationship with Elderly Wife's Depression Level - Setyoadi Setyoadi; Lisa Theana Dewi; Wening Prastowo (Jurusan Keperawatan, Poltekkes Kemenkes Mataram, 2023)
Depression in the elderly is a mental disorder experienced by individuals aged 60 years and over, including feelings of sadness, anxiety, difficulty sleeping and desperation. Depression in wives who are entering old age is a serious mental health problem. Most elderly does not know the symptoms of depression, and it make it difficult for them to adjust to the stressors. The husband is the main source of support for the wife in maintaining her health. The purpose of this study was to determine the correlation between husband's support and the incidence of depression wife among elderlies. This research was an analytic descriptive correlation study with a cross sectional approach. The research sample is 40 wives chosen by purposive sampling with inclusion criteria: 60-90 years old; still had husbands; lived with their husbands; experiencing depression. The research instruments were the Geriatric Depression Scale (GDS) questionnaire and the husband support questionnaire developed by the researchers. The data analysis using Spearman Rank correlation test. The results showed that 22 respondents (55%) had sufficient support from husband; 17 respondents (42.5%) experienced mild depression, and there was a correlation between husband support and the wife's depression level (p-value=0.000) and the value of the correlation coefficient (r)=-0.648. It is suggested that community nurses and cadres for elderlies involve the husbands to provide support for their wives to prevent depression